The Potential of 3D Augmented Reality Book-Based Cell Learning Media to Support Educational Transformation - Triyanto, Samuel Agus; Bilbina, Kanza; Putri, Resa Sohib (Biosfer: Jurnal Pendidikan Biologi, 2025)
Augmented Reality Book is a learning media that utilizes metaverse technology to convert 2D objects into 3D, as an educational transformation in the era of the industrial revolution 4.0. This innovation aims to facilitate students in understanding cell material more deeply and thoroughly. This study aims to analyze the use, utilization, and influence of 3D Augmented Reality Book-based learning media in supporting educational transformation in the era of the industrial revolution 4.0, as well as to determine its impact on students' understanding of cell material. The method used in this research is a literature study, by collecting data and information from various references, such as international and national journals, scientific articles, theses, news, official websites of institutions, and other supporting documents. The secondary data collected is then analyzed to produce the conclusion that the use of 3D Augmented Reality Book can help students understand cell material thoroughly